Estimation of skin dose rate from a catheter bag filled with P-32 solution. Issue 6 (June 2015) - Cockburn, Katrina C.; Moore, Craig S.; Wright, Graham A.
Abstract : Patients attending for therapy with phosphorus-32 (P-32) may have problems with urinary continence requiring the use of a urinary catheter. P-32 is excreted renally and the contents of the catheter bag will impart a dose to the skin with which the bag is in contact. We simulated a catheter bag filled with P-32-contaminated urine and measured the dose rate per unit activity from the bag. A volume of 25 MBq of P-32 was added to a 500 ml bag of saline and mixed thoroughly. A personal dosimetry badge was fixed to the surface of the bag and left for 48 h before being sent for processing. To account for decay, the cumulative activity in the bag over the 48 h period was calculated and the shallow [Hp(0.07)] dose measured by the badge was divided by the cumulative activity to yield a dose rate per MBq of activity. The measured Hp(0.07) dose was 192.8 mSv, which corresponds to a dose rate per MBq of 169 μSv/h/MBq. This study has shown that the dose rate per MBq from a simulated catheter bag of radioactive phosphorus differs from the dose rates published for other containers. This value may be useful in the risk assessment of P-32 therapy in catheterized patients.